SOCIOECONOMIC DETERMINANTS OF POVERTY STATUS AMONG LOWLAND RICE FARMERS IN KOGI STATE - Halliru, M.; Umar, S.; Shuaib, K.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the socioeconomic determinants of poverty status among lowland rice farmers in Kogi State, Nigeria. The specific objectives of the study were to describe the socioeconomic characteristics of the farmers, estimate their poverty status, estimate the determinants of poverty among the farmers respectively. A multistage sampling technique was employed to select 218 respondents across flood-prone communities. Data were collected using structured questionnaires and analyzed through descriptive statistics and inferential statistics (FGT Model, PSM/Logistic regression). The findings revealed that most rice farmers were male, within the economically active age associated with low educational attainment and a high dependence on farming. The poverty assessment showed that a large proportion of respondents (66.06%) live below the poverty line, with noticeable depth (0.499) and severity (0.541). The results of poverty determinants indicated that age, household size, annual income and extension contact were significant at 1% (P<0.01) while gender were reported significant at 5% (P<0.05). The study concludes that over 50% of the respondents were living below the poverty line with an excessive poverty gap that requires critical attention for livelihood improvement. the key variables determining poverty status in the study area include annual income, contact to extension agents and household size among others. It recommends the development of context-specific flood mitigation infrastructure, improved access to agricultural inputs and credit, and strengthened extension services to build resilience and reduce rural poverty.